Avaliação do impacto da capacitação de colaboradores na satisfação dos usuários dos restaurantes universitários da UFSM - Simões, Tiane Tambara (2015)
The term satisfaction can be regarded as the idea formed during or after use or consumption of products or services from a specific supplier (SOLOMON, 2002). Nevertheless, improved human capital, humanware, is essential to provide customer satisfaction and that can be done through education and training, in other words, by adding knowledge, skills improvement, forming good habits and finally indicating individual professional development perspectives (CASTELLI, 2010). Hence, this research aimed to assess the impacts of employee training on the user satisfaction in the University Restaurants of Federal University of Santa Maria UFSM. 116 collaborators (in-house and third-party administrative technician from UFSM) participated in this research, where, in the first and second step of this study, users (students, administrative technician, teachers and visitors) from the three units of the University Restaurant replied to 919 and 274 questionnaires about satisfaction, respectively. In the first step of this research a satisfaction survey was carried out with the restaurant customers, covering the following items: satisfaction with the external and internal (refectory and bathrooms) environment, food (buffet and menu) and attendance (employees and others). Concomitantly with the application of the user satisfaction survey, the Verification List of Good Practices for Food Services, from Portaria nº78/2009 (SECRETARIA DA SAÚDE DO RS, 2009), was also applied in order to verify the level of adequacy related to Good Practices according to legislation. After the application of the user satisfaction survey, a training with all the collaborators from the three units of the University Restaurant was carried out followed by the new application of the satisfaction survey together with the RU users of UFSM. It was also reapplied the Verification List of Good Practices for Food Services from Portaria nº78/2009. The results of this research show that, after the employee training, the satisfaction percentage of several items of the survey increased compared to the results obtained in the first satisfaction survey. Furthermore, the level of adequacy of RU Campus I, related to Good Practices, also increased, passing from 88,7% to 90,6% of adequacy. These results reinforce the idea that employee education and training can be excellent tools to ensure the quality of the services.